Chimeric Peptide Tat-HA-NR2B9c Improves Regenerative Repair after Transient Global Ischemia - Zhou, Hai-Hui; Zhang, Li; Zhang, Hai-Xia; Zhang, Jin-Ping; Ge, Wei-Hong (Frontiers in Neurology, 2017)
Transient global ischemia (TGI) is a major public health problem, it heighten the need of effective treatments. The present study was undertaken to investigate whether recombinant polypeptide Tat-HA-NR2B9c improve spatial learning and memory deficits in rats after transient global ischemia. Rats were subjected to 20-min ischemia induced by four-vessel occlusion (4-VO) method and daily injected with Tat-HA-NR2B9c (1.12 mg/kg) for 1 week. Tat-HA-NR2B9c increased CREB activity, up-regulated Bcl-2 expression after treated 24 h. There was a significant increase in dendrite spine density in hippocampal CA1 region and BrdU-positive cells and BrdU/NeuN-positive cells in the dentate gyrus after Tat-HA-NR2B9c treatment, compared with ischemia group at postischemic day 28. Inhibition of the CREB activation by recombinant lentivirus, LV-CREB133-GFP, abolished the up-regulation effects of Tat-HA-NR2B9c on Bcl-2 expression. Moreover, Tat-HA-NR2B9c improved the impaired spatial learning and memory ability in Morris water maze. These results suggest that Tat-HA-NR2B9c substantially ameliorated the TGI-induced loss of dendrite spine in hippocampal CA1, increased neurogenesis in dentate gyrus, and significantly improved cognitive abilities by the CREB pathway in rats after transient global cerebral ischemia. It may be serves as a treatment for TGI.